If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -74 + -6x = 34 Reorder the terms: -74 + 2x + -6x = 34 Combine like terms: 2x + -6x = -4x -74 + -4x = 34 Solving -74 + -4x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '74' to each side of the equation. -74 + 74 + -4x = 34 + 74 Combine like terms: -74 + 74 = 0 0 + -4x = 34 + 74 -4x = 34 + 74 Combine like terms: 34 + 74 = 108 -4x = 108 Divide each side by '-4'. x = -27 Simplifying x = -27
| 1/2(7x-6)=x-10 | | 6ln(x+9)-7lnx= | | p/s=20 | | 4x^2+12x+9=5 | | 9t-7=t+25 | | 5x-2/3 | | 4t-7=t+25 | | log(5x)=-1 | | 5(4y+3)=8 | | y/5.2=3.4=4.3 | | (8-6i)-(-7+i)= | | 3ax^2+2ax+1=0 | | 0=-1.225x^2+1.73x+1 | | 3s+20=4s | | (a-bi)((a+bi)+1)=11+3i | | -x+2x-1=0 | | 650+88m=650m | | 247*11= | | 2x-14=x+40 | | 0=-12x^2+156x | | 6[1-(5x-2)]=8(3-3x) | | 4q-34=2q | | 3x+15=1x+21 | | 40c^2/8c | | z(z+1)=11+3i | | 7+2z=13 | | 4q-34=29 | | -12x^2+12=156x | | 6p+27=9p | | ax^2+12x+9=0 | | −5=f/5 | | z(z-1)(z+3)=11+3i |